2018
DOI: 10.1111/1744-9987.12768
|View full text |Cite
|
Sign up to set email alerts
|

Is Plasma Exchange Efficacious in Shiga Toxin‐Associated Hemolytic Uremic Syndrome? A Narrative Review of Current Evidence

Abstract: Shiga toxin‐associated hemolytic uremic syndrome (STEC‐HUS) is associated with significant mortality and morbidity. Case fatalities are often associated with severe neurological involvement in children and advanced age in adults but specific treatment is currently unavailable. Plasma exchange (PE) could theoretically enable removal of Shiga toxins, pro‐inflammatory cytokines, and prothrombotic factors and has been used in deteriorating patients with STEC‐HUS but the efficacy remains uncertain. In order to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Evidence supporting the use of supplemental treatments, such as PE or eculizumab, in STEC-HUS is lacking [48][49][50][51]. Extensive cases series and small cohort studies have been published but no randomized control trials have been reported (Supplementary Table 2) [13,15,29,33,34,[37][38][39][40][41][42][43][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the use of supplemental treatments, such as PE or eculizumab, in STEC-HUS is lacking [48][49][50][51]. Extensive cases series and small cohort studies have been published but no randomized control trials have been reported (Supplementary Table 2) [13,15,29,33,34,[37][38][39][40][41][42][43][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Because the effectiveness of specific treatments remains unclear, BSC is the cornerstone of STEC-associated HUS treatment (2,35,36). Univariate analysis indicated that TPE was not associated with overall survival improvement, although other studies have concluded differently (37)(38)(39). However, considering the substantial overlap between the signs and symptoms of STEC-associated HUS in adults and TMA of other etiologies, some researchers believe that plasma therapy should be given until TTP or atypical HUS are ruled out (13,40).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the use of supplemental treatments, such as PE or Eculizumab, in STEC-HUS is lacking. [47][48][49][50] Extensive cases series and small cohort studies have been published but no randomized control trials have been reported (Supplementary Table 2). [13,15,29,33,34,[37][38][39][40][41][42][43][51][52][53] Many specialists, whilst cautiously skeptical of the role of such treatments, tend to use supplemental therapies in severe cases of HUS, particularly in the context of CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[13,15,29,33,34,[37][38][39][40][41][42][43][51][52][53] Many specialists, whilst cautiously skeptical of the role of such treatments, tend to use supplemental therapies in severe cases of HUS, particularly in the context of CNS involvement. [47][48][49][50] In our cohort, we reserved additional treatments for children with severe disease, treating 20/202 children (9.9%) with PE, 4/202 (1.9%) with Eculizumab and 4/202 (1.9%) with both. Our initial approach is treatment with PE; reserving Eculizumab for use when prompt initiation of PE is not practicable or if overwhelming multi-system involvement.…”
Section: Discussionmentioning
confidence: 99%